Ślad Jerzego Pleśniarowicza pozostawiony w przekładach - Buczek, Marta (Przekłady Literatur Słowiańskich, 2020)
This article focuses on the career of Jerzy Pleśniarowicz, the well-known poet of the Józef Czechowicz group and Polish translator of Slavic literatures, as well as dramatist and theatre director. A discussion of the output of this poet and translator is accompanied by an analysis of his Polish translations of Slovak poetry presented in the 2018 volume Wiersze i przekłady wierszy (Poems and Translated Poems). The article considers Pleśniarowicz’s translation choices, elucidates his translation strategies, and discusses the contemporary significance of this poetry within the Polish sphere of reception.